Mortality, length of hospital stay, and nutritional status improvement in severely malnourished children with HIV infection in a tertiary center - Yoga Devaera (Indonesian Pediatric Society, 2012)
Background Severe malnutrition contributes to child mortalityrates, especially in children under five HIV infection further increases the risk of death.Objective To evaluate the impact of HIV infection on mortality,length of hospital stay and improvement of nutritional status inseverely malnourished inpatients under five Methods This retrospective study included children aged less than5 years and admitted to a terti ary hospital for severe malnutrition.We excluded those with incomplete data, as well as thosetransferred to other hospitals or discharged against medical advice.Outcome measures were live/death status, length of hospital stayand improvement of nutritional status (weight gain and improvedweightô€€forô€€height Z score).Results Of 104 eligible patients, 97 were included as studysubjects. Their mean ages were 25.8 (SD 17.3) months forHIY-infected children and 16.3 (SD 15.3) months for HIYuninfectedchildren. Death occurred in 31.8% and 18.7% ofHIVô€€infected and uninfected subjects, respectively. Medianlength of hospital stay was 14.5 (range 5ô€€51) days and 11(range 1ô€€99) days, respectively. There were no statisticallysignificant differences in between the two groups. Weightô€€forô€€height Z scores (WHZ) onadmission and discharge in HIVô€€infected children were lowerthan those of uninfected children, but the weight gain (medianweight gain of 0.45 (-0.26 to 1.9) kg vs 0.38 (-0.81 to 2.2) kgin HIVô€€infected and uninfected children, respectively) andimprovement of WHZ [1 (SD 1.1) vs 0.9 (SD 1), respectively]were similar.Conc l usion Severely malnourished children with HIVinfection had higher mortality rate, and longer hospitalizationsthan the uninfected group, although the differences were notstatistically signific ant. They also had lower mean WHZ scoresat admission and discharge, butnutritionalimprovement wassimilar to those who were HIVô€€negative. [Paediatr Indones.2012;52:362-6].